2015
DOI: 10.1007/s10557-015-6570-0
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Decrease in ATP-Binding Cassette Transporter A1 Expression via microRNA33 Induction may Counteract Cholesterol Efflux to High-Density Lipoprotein

Abstract: In vitro, statins increase miR33 expression, and decrease ABCA1 expression and cholesterol efflux from peripheral tissues; this may counteract the potential benefit of agents that raise HDL and apolipoprotein A-I in statin-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
3
56
0
2
Order By: Relevance
“…49 Niesor et al even reported unfavorable properties of statins regarding HDL-facilitated cholesterol efflux. 163 Statin exposure of cholesterol-loaded human macrophages led to the upregulation of miR-33 mRNA expression, reducing both ABCA1 mRNA expression and ABCA1-mediated cholesterol efflux. 163 Interestingly, by the same mechanism, concomitant statin treatment compromised the positive effects of other HDL-raising drugs, such as the CETP-inhibitor dalcetrapib, on cholesterol efflux capacity.…”
Section: Statinsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Niesor et al even reported unfavorable properties of statins regarding HDL-facilitated cholesterol efflux. 163 Statin exposure of cholesterol-loaded human macrophages led to the upregulation of miR-33 mRNA expression, reducing both ABCA1 mRNA expression and ABCA1-mediated cholesterol efflux. 163 Interestingly, by the same mechanism, concomitant statin treatment compromised the positive effects of other HDL-raising drugs, such as the CETP-inhibitor dalcetrapib, on cholesterol efflux capacity.…”
Section: Statinsmentioning
confidence: 99%
“…163 Statin exposure of cholesterol-loaded human macrophages led to the upregulation of miR-33 mRNA expression, reducing both ABCA1 mRNA expression and ABCA1-mediated cholesterol efflux. 163 Interestingly, by the same mechanism, concomitant statin treatment compromised the positive effects of other HDL-raising drugs, such as the CETP-inhibitor dalcetrapib, on cholesterol efflux capacity. 163 Thus, one may speculate that the effects of statins on macrophage miR-33 expression interfere with the efficacy of CETP inhibitors in statin-treated patients.…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Statins increase expression of miR-33 and result in inhibited ATP-binding cassette transporter (ABCA1) expression. 15,17 In J774 cells, incubation with statins, particularly simvastatin, impairs total cholesterol efflux capacity and ABCA1-specific efflux in a dose-dependent manner. 17 However, differences in total cholesterol efflux capacity and ABCA1-specific efflux capacity between near equipotent doses of other statins have been inconsistent in 2 published reports.…”
Section: Clinical Trials Hdl Cholesterol and Concomitant Use Of Higmentioning
confidence: 99%
“…15,17 In J774 cells, incubation with statins, particularly simvastatin, impairs total cholesterol efflux capacity and ABCA1-specific efflux in a dose-dependent manner. 17 However, differences in total cholesterol efflux capacity and ABCA1-specific efflux capacity between near equipotent doses of other statins have been inconsistent in 2 published reports. 15,17 These data suggest that high-intensity statin therapy may counteract the effect of HDL therapies through miR33-induced downregulation of ABCA1-mediated cholesterol efflux and provide one potential mechanism for the lack of efficacy of HDL-raising therapies in clinical trials in which all participants received statin therapy.…”
Section: Clinical Trials Hdl Cholesterol and Concomitant Use Of Higmentioning
confidence: 99%